Triple therapy for all patients with severe symptomatic COPD at risk of exacerbations. Issue 4 (18th April 2019) - Papi, Alberto; Petruzzelli, Stefano; Vezzoli, Stefano; Georges, George; Fabbri, Leonardo M.
Suissa and Ariel [1] performed a post hoc analysis of TRIBUTE and IMPACT [2, 3], by "digitising" the figures to obtain values over each month of the cumulative incidence curves. They concluded that the lower rate of a first exacerbation with triple long-acting muscarinic antagonist/long-acting β2 -agonist/inhaled corticosteroid (LAMA/LABA/ICS) therapy was exclusively due to a lower rate in the first month of treatment, while the rates were comparable to LAMA/LABA in the subsequent 11 months. They argue that this pattern of "depletion of susceptible individuals" might identify a small group of patients and suggest that only these patients could benefit from triple therapy, whereas the majority could be treated with LAMA/LABA without risk. They also found that the 42% lower mortality with triple therapy in IMPACT was localised in the first 4 months of follow-up, with no difference in the following 8 months. Based on these observations, they speculate that the subgroup who may benefit from triple therapy could be represented by patients with a history of asthma or eosinophilia, and they could be identified a priori . In keeping with the latest international recommendations, we suggest using triple therapy in all patients with severe symptomatic COPD at increased risk of exacerbation who are not adequately treated by LAMA/LABA or LABA/ICS, independent of asthma history http://ow.ly/Bbsr30nXffO